The Program - Kapitulik, Eric; MacDonald, Jake (Ascent Audio, 2019)
The Program: Lessons From Elite Military Units for Creating and Sustaining High Performing Leaders and Teams offers a hands-on guide to the winning techniques and tactics of The Program, the acclaimed team building and leadership development company. Drawing on the actual experiences of The Program's instructors from their personal combat stories to working with world-class athletic teams and successful corporations, the book clearly shows how The Program's training operations can help to achieve life goals and ambitions. The Program offers a road map that contains illustrative examples, ideas, and approaches for improving teammates and leaders at all levels within an organization of any size or type. - Bring your organization to the next level of success - Discover how to hold your leaders and teammates to the highest standards - Understand how accountability increases effectiveness - Learn to communicate effectively This important book explores the military's leadership and team building concepts that can be implemented to ensure an organization creates and sustains performance that adheres to the highest standards of excellence.